2019
DOI: 10.1002/mds.27669
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric MRI profiles of multiple system atrophy variants and implications for differential diagnosis

Abstract: Background Manual width measurements of the middle cerebellar peduncle on MRI were shown to improve the accuracy of an imaging‐guided diagnosis of multiple system atrophy (MSA). Recently, automated volume segmentation algorithms were able to reliably differentiate patients with Parkinson's disease (PD) and the parkinsonian variant of MSA. The objective of the current study was to integrate probabilistic information of the middle cerebellar peduncle into an existing MRI atlas for automated subcortical segmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 36 publications
1
43
1
Order By: Relevance
“…The present cohort represents a subset (those patients who have DTI registrations of sufficient quality) of a previously published cohort. 9 The clinical evaluation included the Hoehn and Yahr staging scheme, the Unified Parkinson's Disease Rating Scale, and the Mini-Mental State Examination. All rating scales in patients with PD were performed in the on state.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present cohort represents a subset (those patients who have DTI registrations of sufficient quality) of a previously published cohort. 9 The clinical evaluation included the Hoehn and Yahr staging scheme, the Unified Parkinson's Disease Rating Scale, and the Mini-Mental State Examination. All rating scales in patients with PD were performed in the on state.…”
Section: Patientsmentioning
confidence: 99%
“…[23][24][25][26] Moreover, a published technique to integrate MCP segmentation into FreeSurfer was applied. 9 The preprocessing steps were visually inspected to ensure that no misalignment of brain structures had occurred. We then processed native DTI data and performed structural-to-diffusion data coregistration using FreeSurfer and FMRIB Software Library tools.…”
Section: Magnetic Resonance Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed for the correct diagnosis of MSA‐P versus PD or PSP at the first neurological visit in 100% of patients, substantially improving the clinical diagnostic accuracy of 63% 23 . The combination of automated subcortical and supra‐ and infratentorial segmentation that included the volumetric measure of the MCP confirmed the high diagnostic accuracy of this approach in separating both MSA‐P and MSA‐C from PD 24 . There is yet no comparative data from volumetric studies addressing MSA‐C versus SAOA.…”
Section: Resultsmentioning
confidence: 83%
“…A recent study reported that the clinicopathological consistency of MSA was only 62% (Koga et al, 2015). Multimodal MRI technology is often applied in the diagnosis of MSA patients (Pradhan and Tandon, 2017;Krismer et al, 2019). Several MRI findings have been reported in MSA-P patients, including the presence of a bilateral T2-hyperintense rim bordering the dorsolateral margins of the putamen (the ''HPR sign''), T2-putaminal hypointensity (T2H), and atrophy of the putamen, middle cerebellar peduncles (MCP), cerebellum, or pons (Massey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%